2010
DOI: 10.1159/000312132
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiological Roles of PI3Ks and Therapeutic Potential of Selective Inhibitors in Allergic Inflammation

Abstract: Phosphoinositide 3-kinases (PI3Ks) are known to be involved in a variety of cellular responses such as cell survival, proliferation, differentiation and cell migration. Recently, PI3Ks have been associated with the pathogenesis of asthma because various immune cells regulate allergic responses. Among the three classes of PI3Ks, the roles of PI3Kγ and PI3Kδ in allergic responses have attracted particular attention. In a previous report, allergic airway hyperresponsiveness (AHR), inflammation and airway remodeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 57 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…The effects of IL-25 on angiogenesis were investigated using an in vitro angiogenesis assay (34,35) based on coculture of HUVEC for 11 d over a monolayer of irradiated fibroblasts (AngioKit; TCS CellWorks). Further details are given in SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of IL-25 on angiogenesis were investigated using an in vitro angiogenesis assay (34,35) based on coculture of HUVEC for 11 d over a monolayer of irradiated fibroblasts (AngioKit; TCS CellWorks). Further details are given in SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…The pathogennesis of asthma strongly depends on elevated levels of IgE antibodies and activation of immune cells such as T helper type 2 (T h 2) cells, mast cells, neutrophils, B cells and eosinophils, which produce a number of cytokines, chemokines, adhesion molecules, growth factors and enzymes contributing to disease progression (reviewed in [194]). PI3Ks are part of the complex signaling network involved in asthma development (reviewed in [195,196]). Genetic inactivation of p110δ in ovalbumin (OVA)-challenged mice decreased T h 2 cytokine-dependent airway inflammation, mucus production and reduced eosinophil recruitment [197].…”
Section: Respiratory Diseasesmentioning
confidence: 99%
“…PI3Ks are thought to be involved in a number of pathological states such as cancer, inflammation and allergy. Studies also showed that PI3K pathway plays a crucial role in the pathogenesis of asthma (Kampe et al, 2012;Ro et al, 2013;Takeda et al, 2010). In vitro, PI3K was required for activation of caspase-1, secretion of IL-1b and IL-18, as well as nucleocytoplasmic translocation of HMGB1 (Oh et al, 2009;Tapia-Abellan et al, 2014).…”
Section: Introductionmentioning
confidence: 97%